Internalized skin bias: validation study to explore the impact of the internalization of social stigma on those with hidradenitis suppurativa. (25th February 2022) - Butt, M.; Chinchilli, V.M.; Leslie, D.L.; Khesroh, E.; Helm, M.F.; Flamm, A.; Kirby, J.S.; Rigby, A.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic auto‐inflammatory disease that is highly associated with adverse psychopathology and impaired body image. Previous studies show that patients with HS are also impacted by social stigma associated with their skin disease. Over time, these experiences can influence the way in which patients feel about themselves, leading to internalized skin bias (ISB). Objectives: To evaluate the validity and reliability of the Internalized Skin Bias Questionnaire (ISBQ) in an HS population and to determine the association of this instrument with markers of HS severity. Methods: A cross‐sectional survey with 72‐h retest was sent to adult patients with HS from March to November 2021. Reliability for the ISBQ was evaluated using Cronbach's alpha and the Concordance Correlation Coefficient (CCC). Construct validity was evaluated using Pearson Correlation Coefficients with similar measures. Results: Internal consistency for the ISBQ instrument was 0.89 with a CCC of 0.88. The ISBQ had moderate correlation ( r = 0.63) with the experienced skin stigma questionnaire as well as the BDI‐II ( r = 0.66) and the psychosocial subscale of the HiSQOL ( r = 0.65). ISBQ scores differed significantly across different stages of disease severity ( P = 0.04). There was no significant difference between those with different durations of disease ( P = 0.47). Conclusions: This study shows that the ISBQ is a valid and reliable instrument that can be used to assess the psychosocial construct of ISB especially in a population of HS patients. Further, ISB places a prevalent negative impact on the psychopathology of patients with HS.